2009
DOI: 10.3113/fai.2009.1053
|View full text |Cite
|
Sign up to set email alerts
|

Distal Tendinosis of the Tibialis Anterior Tendon

Abstract: Distal TA tendinosis is a condition that seems to predominantly affect overweight elderly women. It often presents with nocturnal burning medial midfoot pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 29 publications
(43 reference statements)
0
42
0
1
Order By: Relevance
“…It has been reported that downhill running (DR) induces more foot/ankle/lower leg injuries than level running (Buczek and Cavanagh 1990;Gottschall and Kram 2005;Mizrahi et al 2000b), because of greater eccentric muscle contractions imposed in DR. On the other hand, the major locomotor muscles shorten while exerting force during uphill running (UR), in which they consume more energy, resulting in higher metabolic fatigue (Gottschall and Kram 2005). Some authors speculated that tibialis anterior tendonitis/tenosynovitis in runners might be due to an increase in training distance particularly with UR and DR (Beischer et al 2009;Fallon 1996;Bishop and Fallon 1999). However to date, the effects of a long distance run including UR/DR on PF and DF fatigue have not been reported.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been reported that downhill running (DR) induces more foot/ankle/lower leg injuries than level running (Buczek and Cavanagh 1990;Gottschall and Kram 2005;Mizrahi et al 2000b), because of greater eccentric muscle contractions imposed in DR. On the other hand, the major locomotor muscles shorten while exerting force during uphill running (UR), in which they consume more energy, resulting in higher metabolic fatigue (Gottschall and Kram 2005). Some authors speculated that tibialis anterior tendonitis/tenosynovitis in runners might be due to an increase in training distance particularly with UR and DR (Beischer et al 2009;Fallon 1996;Bishop and Fallon 1999). However to date, the effects of a long distance run including UR/DR on PF and DF fatigue have not been reported.…”
Section: Introductionmentioning
confidence: 95%
“…In a review on running injuries, van Gent et al (2007) reported that the predominant site of lower extremity injuries was the knee, but high injury incidence was also observed around the lower leg (shin and calf) and foot, ranging from 9.0 to 32.2% and 5.7 to 39.3%, respectively. Some studies have investigated injuries in ultra-marathons or other types of long distance running activities, and have shown that typical ultra-marathon injuries are tendonitis/tenosynovitis of the ankle dorsal flexor (Beischer et al 2009;Bishop and Fallon 1999;Fallon 1996;Kobayashi et al 2007). Fallon (1996) documented that marked overuse and excessive eccentric loading were associated with the aetiology of typical ultramarathon injuries.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, though the entity of tibialis anterior (TA) tendon rupture has been well reported, 1,4,6,7,13,15,17 -19,22,23,26 -28,30,32 distal tibialis anterior tendinopathy (DTAT) has been infrequently described in the literature. 3,6,10,13,22 The senior author (ADB) has recently reported a review of 29 patients diagnosed with the condition, detailing the clinical features and outlining its radiological features and management. DTAT is predominantly a condition of overweight women in the 50-to 70-year age group.…”
Section: Introductionmentioning
confidence: 99%
“…The tibialis anterior passive stretch (TAPS) test appears to be a useful provocative test. 3 The initial treatment of DTAT is nonoperative with a soft, accommodative, full length, custom orthosis supporting the medial longitudinal arch; non-steroidal anti-inflammatory medication; and, when tolerated, night splints. Should this initial approach fail however, surgery can be considered.…”
Section: Introductionmentioning
confidence: 99%